Swamp : uma metodologia espaço-temporal para análise de dados ambientais usando wavelets e séries temporais - Guarienti, Gracyeli Santos Souza (2018)
The work presents a new temporal vision for the manipulation, modeling and visualization of environmental data. Named SWAmP (Web Geographic Information System for Environmental Precipitation Data), this same methodology is validated with an implementation of the SWAmP 1.0 software, which includes the steps of the methodology in a web GIS interface and the use of data from the TRMM (Project of Precipitation Measurement), and INMET (National Institute of Meteorology). They show that, as the imitation steps of mathematical methods, are present in the SWAmP methodology bring new perspectives for the analysis of environmental data. The tests are of type SWAmP 1.0 are demonstrated with data of precipitation (16 years), mean and average environment between (-8, -22S and -49, -61W) in the years 1998 to 2013.